Teknologi Tepat Guna Alat Distilasi Minyak Serai Wangi Bagi Kelompok Tani Ampek Sarumpun di Dama Gadang - Nadia Alfitri; Yefriadi; Nofriyandi; Albar; Yul Antonisfia (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Dama Gadang is part of Dalko village, which is located in Tanjung Raya sub-district, Agam district, West Sumatra province. Dalko has a topography of 200 m - 500 m above sea level with rainfall of 2500 mm per year. The Dalko topography is very suitable for growing citronella. To be able to fulfill their survival, people in this village are trying to cultivate citronella plants. Efforts to produce citronella oil have been carried out by the Ampek Serumpun farmer group since 2018. The processing of citronella oil which is managed by the farmer group still has many limitations of simple equipment so that the oil produced is also small. Therefore, a citronella oil distillation device was made by adopting appropriate technology that can practically be used by the community. The method of implementing this service activity is to make general observations on the level of community technology understanding about the distillation process, create a concept of training in the use of tools and provide operational assistance for tools. The results of this distillation equipment grant can be implemented by the community in stages and evaluate the production of citronella oil before and after the use of the distillation equipment.